Impact of tiny miRNAs on cancers - Liu, Wei (Baishideng Publishing Group Co., Limited, 2007)
miRNAs are a class of small, ~22nt, non-coding RNAs that negatively regulate gene expression at the post-transcriptional level. They play profound and pervasive roles in manipulating gene expression involved in cell development, proliferation and apoptosis in various eukaryotes, which, in theory, could provide an access to many human diseases in theory. Recent evidence demonstrates that aberrant miRNA expression is a hallmark of tumor development, revealing that miRNA genes could function as potential oncogenes and repressors in the human body. miRNAs can affect tumorigenesis mainly by interrupting the cell cycle at the cellular level and by interacting with signaling, oncogenes and with the response to environmental factors at the molecular level. The established miRNA expression signature could be a potent tool to diagnose and treat human cancers in the future.